A practical lesson in polarization optics: Creating a 3D image using a liquid crystal cell. (24th March 2017) - Polak, Robert D.; Kumar, Akshar; Schmidt, Matthew
ABSTRACT: To demonstrate a practical application of polarization physics, a liquid crystal pi cell is used as a variable retarder to create different types of polarization. By varying the applied voltage to the cell, the polarization of the outgoing light can be controlled. Because of the rapid switching time of the pi cell, it is possible to alternate between orthogonal circular polarizations or orthogonal linear polarizations at a speed faster than can be reconciled by the human eye. Synchronizing images intended for different eyes with the polarization state of the cell, light of orthogonal polarization is incident upon a polarization maintaining screen. Through use of passive glasses that allow one state of polarization to pass while blocking the orthogonal state for each eye, the visual information will create a 3D image in the viewer's mind. The physics behind this can be described using bra-ket notation, and the experimental method is similar to that used in movie theatres and theme park attractions. It can be used as a practical demonstration of polarization physics and liquid crystal physics as well as an experiment in an upper-division laboratory course for physics majors.